2015
DOI: 10.1364/ol.40.004599
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast optical transistor and router of multi-order fluorescence and spontaneous parametric four-wave mixing in Pr^3+:YSO

Abstract: We study the realization of an optical transistor (switch and amplifier) and router in multi-order fluorescence (FL) and spontaneous parametric four-wave mixing (SP-FWM). We estimate that the switching speed is about 15 ns. The router action results from the Autler-Townes splitting in spectral or time domain. The switch and amplifier are realized by dressing suppression and enhancement in FL and SP-FWM. The optical transistor and router can be controlled by multi-parameters (i.e., power, detuning, or polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…We observed that the highest amplification ratio of an optical transistor is about 8.5 from Fig. 2(b) [14].…”
mentioning
confidence: 65%
“…We observed that the highest amplification ratio of an optical transistor is about 8.5 from Fig. 2(b) [14].…”
mentioning
confidence: 65%
“…And the interval between the split energy levels is , where N is the number of excited atoms 14 . A lot of work has been concentrated on VRS of two-level atom system (normal-mode splitting), such as in atomic beams 15 , cold atomic cloud 16 , 17 , and a Bose–Einstein condensate 18 – 20 . Specifically, the normal-mode splitting in case of , corresponding to free spectral region, have been reported widely, which is equated with generation a single cavity resonant mode splitting close to the atomic resonance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the issues including FWM and power consumption in WDM‐based all‐optical networks should be resolved to provide high‐quality and low‐energy communications in near future. As another technique to design low‐power all‐optical networks under the FWM constraint, future all‐optical devices have been considered in the past . The proposed method focuses on a route, wavelength, and fiber selection algorithm in the upper layer, and thus, it works on such all‐optical devices in the lower layer.…”
Section: Introductionmentioning
confidence: 99%